Zjawisko przeedukowania i inflacji dyplomu akademickiego – na przykładzie spo-łeczeństwa amerykańskiego - Sobczak, Anna (Studia Edukacyjne, 2018)
Democratization and massification of higher education has resulted in the appearance of a disadvan-tageous phenomenon known as the overeducation of society. The term refers to a situation in which there is a surplus of people with higher education in relation to the needs of the society and the labor market. This has led to academic diploma inflation, which does not have such a high value as it used to and currently does not guarantee professional success and high social status. The aim of the article is to present selected aspects of this problem in American society. In this study, the definitions of the eponymous phenomenon are presented as well as statistical data and the main trends regarding the overeducation of the society in the United States.